Early Warning Systems for banking crises: political and economic stability - Tamadonejad, Alireza; Mariani Abdul-Majid,; Aisyah Abdul-Rahman,; Mansor Jusoh,; Razieh Tabandeh, (Penerbit Universiti Kebangsaan Malaysia, 2016)
Early Warning System (EWS) is a system that tries to predict the probability of crises using environmental factors. This study seeks to develop an EWS for the probability of systemic banking crises in East Asian countries by using a logit model taking into account a wide range of political and economic factors. Results reveal that short-term debt and exchange rate depreciation may trigger speculative attacks during political instability, economic slowdown, and inefficient regulatory environments. Policymakers and regulators may be able to prevent crises by stabilizing political and economic conditions. Furthermore, results indicate that government instability, corruption, high short-term debt, unstable monetary and fiscal policies do not only reduce investors’ confidence but also prevent effective crisis prevention strategies. Therefore, by adopting the EWS the government would be able to monitor environmental changes causing crises.